Innovative Work Behaviour: A Bibliometric Analysis and Future Research Directions - Nor, Khalijah Binti Mohd; Hashim, Wan Nor Syazana Wan; Jislan, Fatanah; Ahmad, Nurbarirah (Global business and management research, 2024)
The main driver of organization development and competitive advantage is innovation. The increases in change in a variety of business sectors throughout the world, demand that businesses and institutions come up with innovative solutions to problems in order to perform well. In this paper, a bibliometric analysis is conducted to determine the evolution of publications on innovative work behaviour. Originality/value: This study has direct implications for academics in positioning their future research. The increasing importance of the assessment of scientific production has also made bibliometric studies have significant implications for universities and policymakers.